Intra‐ and interspecific variation in macaque molar enamel thickness. Issue 3 (22nd August 2014) - Kato, Akiko; Tang, Nancy; Borries, Carola; Papakyrikos, Amanda M.; Hinde, Katie; Miller, Ellen; Kunimatsu, Yutaka; Hirasaki, Eishi; Shimizu, Daisuke; Smith, Tanya M.
ABSTRACT Enamel thickness has played an important role in studies of primate taxonomy, phylogeny, and functional morphology, although its variation among hominins is poorly understood. Macaques parallel hominins in their widespread geographic distribution, relative range of body sizes, and radiation during the last five million years. To explore enamel thickness variation, we quantified average and relative enamel thickness (AET and RET) in Macaca arctoides, Macaca fascicularis, Macaca fuscata, Macaca mulatta, Macaca nemestrina, and Macaca sylvanus. Enamel area, dentine area, and enamel‐dentine junction length were measured from mesial sections of 386 molars scanned with micro‐computed tomography, yielding AET and RET indices. Intraspecific sex differences were not found in AET or RET. Macaca fuscata had the highest AET and RET, M. fascicularis showed the lowest AET, and M. arctoides had the lowest RET. The latitudinal distribution of macaque species was associated with AET for these six species. Temperate macaques had thicker molar enamel than did tropical macaques, suggesting that thick enamel may be adaptive in seasonal environments. Additional research is needed to determine if thick enamel in temperate macaques is a response to intensified hard‐object feeding, increased abrasion, and/or a broader diet with a greater range of food material properties. The extreme ecological flexibility of macaques may prohibit identification of consistent trends between specific diets and enamel thickness conditions. Such complications of interpretation of ecological variability, dietary diversity, and enamel thickness may similarly apply for fossil Homo species. Am J Phys Anthropol 155:447–459, 2014. © 2014 Wiley Periodicals, Inc.